PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI ANAK USIA DINI - Mahdi M. Ali (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2015)
This study examines the teaching of Islamic Religious Education (PAI) for Young Children at Pocut Baren Kindergarten Padang Tiji in the District of Pidie by analyzing learning activities, from the perspectives of curriculum and teaching materials as well as planning and the evaluation system. We utilize a descriptive-analytic approach to field research and look at a variety of literature relevant to teaching religion to young children as a theoretical foundation for our research.The review of school document, field observations, and interviews with the head of the kindergarten and teachers are an integral part of our analytical approach. Our study finds that the teachers of this kindergarten understand the curriculum and have proficiently designed the study plans even though their implementation are at times isolated from the already-designed daily and weekly sketches (SKH and SKM).Furthermore, the evaluation of Islamic religious education in this school is conducted daily and semi-annually (every semester) and the results of both tests indicate the overall progress and achievement of pupils. All of this illustrates that the implementation of Islamic religious education at Pocut Baren Kindergarten Padang Tiji has proceeded adequately for the purpose of achieving educational objectives stated in the curriculum. Yet, it still needs the principal’s and teachers’ further innovation and creativity, so that the teaching and learning processes become richer and are in accordance with the development of scientific progress and the dynamics of the new era.